Hero mounted on a horse accompanied by a celestial damsel - Temples of India Project Team (Jio Institute, 2024)
A hero stones fragment measures about a foot in height and half a foot in width, featuring a slightly different depiction than the other hero stones. In this fragment, the hero is portrayed mounted on horse, accompanied not by a celestial damsel but by another human figure kneeling down. This second figure could also be a depiction of the hero. The scene symbolizes the hero’s journey to heaven after his death, where he bows down to God, often represented by depicted Shiva in his linga (aninconic representation of Shiva) form. The undulating stone surface of the hero stones makes it difficult to understand whether it originally contained any inscriptions.